PENENTUAN KADAR OKSIGEN TERLARUT MENGGUNAKAN SENSOR POLAROGRAFI BERMEMBRAN PLASTIK (Determination of dissolved oxygen with polarographic oxygen sensor plastic membrane probe) - Suhanda, Hokcu (Jurnal Pengajaran MIPA, 2001)
Plastic membrane sensor for polarographic oxygen measurement has been investigated. The Probe was constructed of: Pt as a working electrode; Ag-AgCl as a reference electrode and an auxiliary electrode; solution of KCl as an electrolyte solution; plastic wrap (thickness 72.7 mm) as a membrane; and polyester polymer as a body of sensor. It was found that the polarographic oxygen sensor plastic membrane probe was suited for determination of dissolved oxygen with an optimum operating characteristics at applied voltage of  –0.65 V and solution KCl 30% as an electrolyte. The probe showed that reduction current achieved steady state after 75 seconds. The standard calibration curve (concentration – current) showed that the linear relationships were achieved for dissolved oxygen in the range of 1.0 – 30.6 ppm.The analytical performance characteristics of the probe were: precision 0.87% – 30.0 %; calibration sensitivity 0.17 ppm/mA; analytical sensitivity 0.56 – 0.84 ppm/mA; and detection limit 0.8 ppm. The t- test and F-test at 95% confidence level showed that there was no significant difference between the determinations of dissolved oxygen by polarographic oxygen sensor membrane plastic and by Winkler method.